« La triste Touggourt endormie sous son suaire de sel » L’écriture autobiogéographique dans les Premier et Deuxième Journaliers d’Isabelle Eberhardt - Sokołowicz, Małgorzata (Romanica Silesiana, 2024)
The paper argues that the first and second Journaliers, a sort of diary kept by Isabelle Eberhardt (1877–1904), a Suisse writer and traveler of Russian origins, may be considered as autobiogeographical. The term autobiogeography has been coined at the beginning of the 21st century and describes the interactions between the autobiographical self and geography, or space. The autobiogeographical character of two first Journaliers is presented in three parts. The first focuses on the specificity of the text and its relationship with geography. The second talks about the links between particular cities and the Eberhardtian self. The third depicts the relationships between the self and the landscape: not only does it show how geography influences the self, but also what the impact of the self is on the way we look at the space.